2000
DOI: 10.1063/1.870313
|View full text |Cite
|
Sign up to set email alerts
|

A low-dimensional approach to nonlinear plane-Couette flow of viscoelastic fluids

Abstract: The nonlinear stability of the one-dimensional plane Couette flow is examined for a Johnson–Segalman fluid. The velocity and stress are represented by symmetric and antisymmetric Chandrasekhar functions in space. The flow field is obtained from the conservation and constitutive equations using the Galerkin projection method. Both inertia and normal stress effects are included. For given Reynolds number and viscosity ratio, two critical Weissenberg numbers are found at which an exchange of stability occurs betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…It is tempting to speculate that the numerical instability observed by Atalik and Keunings is a manifestation of the underlying physical instability. Ashrafi and Khayat (Ashrafi and Khayat, 2000) have developed a low-dimensional Galerkin projection for the Johnson-Segalman fluid, and have shown that one-dimensional disturbances in x-direction become unstable. There as well, one cannot draw a conclusion about the resulting state in view of the special form of the perturbation and the very small number of modes included.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that the numerical instability observed by Atalik and Keunings is a manifestation of the underlying physical instability. Ashrafi and Khayat (Ashrafi and Khayat, 2000) have developed a low-dimensional Galerkin projection for the Johnson-Segalman fluid, and have shown that one-dimensional disturbances in x-direction become unstable. There as well, one cannot draw a conclusion about the resulting state in view of the special form of the perturbation and the very small number of modes included.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of problem formulation is given for the channel ow of a Johnson-Segalman (JS) uid. Details of formulation and solution procedure as well as additional results are given elsewhere [11]. Only one-dimensional ow is considered.…”
Section: Problem Formulation and Solution For Channel Flowmentioning
confidence: 99%
“…These techniques have been explored by Khayat [12] for various non-linear and non-Newtonian problems in hydrodynamic stability. In this paper, only a summary of methodology and results relevant to fully developed PCF are reported, leaving the details to Reference [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations